Pseudomonas aeruginosa mexR and mexEF Antibiotic Efflux Pump Variants Exhibit Increased Virulence - Mylene Vaillancourt; Sam P. Limsuwannarot; Catherine Bresee; Rahgavi Poopalarajah; Peter Jorth (MDPI AG, 2021)
Antibiotic-resistant Pseudomonas aeruginosa infections are the primary cause of mortality in people with cystic fibrosis (CF). Yet, it has only recently become appreciated that resistance mutations can also increase P. aeruginosa virulence, even in the absence of antibiotics. Moreover, the mechanisms by which resistance mutations increase virulence are poorly understood. In this study we tested the hypothesis that mutations affecting efflux pumps can directly increase P. aeruginosa virulence. Using genetics, physiological assays, and model infections, we show that efflux pump mutations can increase virulence. Mutations of the mexEF efflux pump system increased swarming, rhamnolipid production, and lethality in a mouse infection model, while mutations in mexR that increased expression of the mexAB-oprM efflux system increased virulence during an acute murine lung infection without affecting swarming or rhamnolipid gene expression. Finally, we show that an efflux pump inhibitor, which represents a proposed novel treatment approach for P. aeruginosa, increased rhamnolipid gene expression in a dose-dependent manner. This finding is important because rhamnolipids are key virulence factors involved in dissemination through epithelial barriers and cause neutrophil necrosis. Together, these data show how current and proposed future anti-Pseudomonal treatments may unintentionally make infections worse by increasing virulence. Therefore, treatments that target efflux should be pursued with caution.